PERTUMBUHAN STEK TANAMAN TEBU (Sacharum officinarum.L) SETELAH PERENDAMAN DENGAN AIR BAWANG MERAH (Allium Cepa.L) - Mulyanti, Mulyanti (Universitas Gajah Putih, 2025)
Propagation of sugarcane plants is basically done vegetatively. The success of sugarcane cuttings is inseparable from the use of growth stimulants (ZPT). Shallots, apart from containing the hormone auxin, are also known to contain the compound allithianin which functions to facilitate metabolism in plant cell tissues and can also function as a fungicide and bactericidal. This study aims to determine the effect of shallot water growth regulators and to determine the effective soaking time on the growth of shoots of sugarcane cuttings. This study used a non-factorial randomized block design (RBD) with 4 (four) treatments and 6 repetitions so that there were 24 experimental units. The order of treatment was T0 (without soaking in shallot water), T1 (soaking in shallot water for 1 hour), T2 (soaking in shallot water for 2 hours), and T3 (soaking in shallot water for 3 hours). Parameters observed were shoot length, number of leaves and stem diameter of sugarcane cuttings. The results showed that the sugarcane cuttings after being soaked in shallot water at different times had a very significant effect on the shoot length and stem diameter of the sugarcane cuttings, and had no significant effect on the number of leaves. The best treatment was obtained at T3 (soaking for 3 hours).